An Investigation of Surgical Nurses' Professional Values, Ethical Sensitivity and Quality of Care: A Cross-Sectional Study From Northwest Turkey. Issue 1 (March 2023) - Mert, Selda; Kersu, Özlem; Aydin Sayilan, Aylin; Akyolcu, Neriman
Nurses' professional values are closely associated with their ethical sensitivity and the quality of nursing care. The aim of this study was to determine surgical nurses' perceptions of their professional values, ethical sensitivities and quality of care, the relationship between these variables, and the factors influencing these. The sample of this cross-sectional, descriptive and relational study consisted of 231 nurses working in the surgical units of two university hospitals and a training and research hospital. The study revealed a statistically significant negative relationship between the nurses' professional values scale median score and the Moral Sensitivity Questionnaire median score, and a positive significant relationship between the Nurses' Professional Values Scale median score and the Care Behaviors Scale median score. Having ethical problems in their professional lives increased the ethical sensitivity of nurses, while having a medical-vocational high school and vocational school of health services degree and participation in training/meetings about professional values and ethics increased the perception of the quality of nursing care. Awareness of professional values is crucial in providing quality nursing care that is in line with ethical principles; therefore, it is recommended that the continuity of surgical nurses' participation in training/meetings on professional values and ethics be ensured, that they be supported to become members of professional associations, and that supportive working environments be provided to improve the quality of nursing care.